2011
DOI: 10.1111/j.1743-7563.2011.01464.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of tumor lysis syndrome with a single fixed dose of rasburicase in Asian lymphoma patients: A case series and literature review

Abstract: Among Asian lymphoma patients who manifested at least two risk factors for developing TLS, a single fixed dose of rasburicase at 6 mg is deemed to be effective for rapidly lowering uric acid levels as well as sustaining reduced levels for up to 72 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…One single 3mg rasburicase can prevent TLS in majority of adult high risk haematological malignancies patients, however, close monitor for biochemical and clinical markers of TLS is necessary; once there is any progression evidence, the dose should be repeated daily until TLS markers return to normal; furthermore, if clinical TLS still worsens, rasburicase should be used with a standard dose (0.2mg/kg/day) [17]. A case series of adult lymphoma patients presenting the high risk of TLS received a single xed dose of rasburicase (6mg or 4.5mg) and obtained an improvement of the mean uric acid level and renal function [18]. In the current case, high tumor cells burden, the patient not seeing doctor in time, the delayed con rmative diagnosis because of the two times of pathological investigation, repeated and plausible "routine" glucocorticoids using after stent implanting and the time that he complaining chest tight, lack of rasburicase supplying, multiple disciplinary team communication being not enough timely, all of above contributed to initiation and progression of TLS.…”
Section: Discussionmentioning
confidence: 99%
“…One single 3mg rasburicase can prevent TLS in majority of adult high risk haematological malignancies patients, however, close monitor for biochemical and clinical markers of TLS is necessary; once there is any progression evidence, the dose should be repeated daily until TLS markers return to normal; furthermore, if clinical TLS still worsens, rasburicase should be used with a standard dose (0.2mg/kg/day) [17]. A case series of adult lymphoma patients presenting the high risk of TLS received a single xed dose of rasburicase (6mg or 4.5mg) and obtained an improvement of the mean uric acid level and renal function [18]. In the current case, high tumor cells burden, the patient not seeing doctor in time, the delayed con rmative diagnosis because of the two times of pathological investigation, repeated and plausible "routine" glucocorticoids using after stent implanting and the time that he complaining chest tight, lack of rasburicase supplying, multiple disciplinary team communication being not enough timely, all of above contributed to initiation and progression of TLS.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies and published guidelines have shown cumulative support for the safe and efficacious use of offlabel dosing regimens of rasburicase [1, 5-8, 10,11,16,17]. A quarter of our patients presented with a baseline WCC>100 ¥ 10 9 l -1 (Table 1), which is considered a high risk for developing TLS [1, 7].…”
mentioning
confidence: 97%
“…Newer guidelines now include rasburicase, with monitoring of electrolytes, white blood cell counts (WCC) and lactate dehydrogenase (LDH) concentrations [1, 7,8].Rasburicase, a recombinant urate oxidase enzyme, effectively decreases existing serum uric acid (UA) by oxidizing it to allantoin which is readily soluble and excretable [3]. Although the recommended dose is 0.2 mg kg -1 day -1 for 5-7 days [9], studies have shown the efficacious use of reduced doses for shorter periods of time and subsequent cost savings [5, 6,[10][11][12][13][14][15][16][17].Expert guidelines by Coieffer et al [7] in 2008 and Cairo et al in 2010 [1] on the management of TLS recommend a rasburicase dose of 0.1-0.2 mg kg -1 on the first day, then repeated for up to 7 days [1] or as necessary [7].We present an analysis of a fixed 3 mg dose of rasburicase administered to adult patients, treated at a tertiary referral centre. The study was approved by the Alfred Health Human Research Ethics Committee and the Monash University Human Research Ethics Committee.Demographic data were collected.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 The quality of submitted and accepted original articles has increased substantially in the last 12-18 months, and should in time lead to increased citations of APJCO papers in the cancer literature. Some highlights from the original articles submitted include: Cancer in Australia, an assessment of the incidence and mortality of cancer for the whole country, published in December; 4 an evaluation of an electronic website that provides high-quality peer-reviewed information about treatment protocols for malignancy; 5 rasburicase to treat tumour lysis syndrome in lymphoma patients; 6 a review of technical issues in relation to mammography and the potential adverse implications of a move to digital mammography; 7 and 2 papers related to issues in cervical cancer and HPV vaccination in less developed regions. 8,9 The Journal is clearly showing increased value to a wide range of oncologists globally, particularly in the AsiaPacific region.…”
mentioning
confidence: 99%